1977
DOI: 10.1111/j.1476-5381.1977.tb08395.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuroleptics and Other Drugs on Monoamine Uptake by Membranes of Adrenal Chromaffin Granules

Abstract: The effects have been investigated of various reserpine‐like, neuroleptic, antidepressant and other compounds on the adenosine‐5′‐triphosphate (ATP)‐dependent uptake of noradrenaline (NA) (reserpine‐sensitive) and tryptamine (reserpine‐resistant) by membranes of isolated chromaffin granules of bovine adrenal medulla. Reserpine and Ro 4–1284 (2‐hydroxy‐2‐ethyl‐3‐isobutyl‐9,10‐dimethoxy‐hexahydro‐11bH‐benzo(a)quinolizine) as well as neuroleptics (e.g. chlorpromazine and haloperidol) inhibited the NA uptake, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Diazepam 1 mg· kg -I failed to significantly alter the uptake of intracerebroventricularly injected 3H-NA (NAKAMURA and THOENEN, 1972). Benzodiazepines were very weak inhibitors of the uptake of 14C_NA by isolated membranes of bovine adrenal medulla (PLETSCHER, 1977); the IC 50 were 7x 10-5 mol·l-I and 5x 10-4 mol·l-I for diazepam and chlordiazepoxide, respectively. TAYLOR andLAVERTY (1969, 1973) found the uptake or 3H-NA into synaptosomes of rat hypothalamus hardly affected by even high concentrations of benzodiazepines.…”
Section: Noradrenaline (Na)mentioning
confidence: 96%
“…Diazepam 1 mg· kg -I failed to significantly alter the uptake of intracerebroventricularly injected 3H-NA (NAKAMURA and THOENEN, 1972). Benzodiazepines were very weak inhibitors of the uptake of 14C_NA by isolated membranes of bovine adrenal medulla (PLETSCHER, 1977); the IC 50 were 7x 10-5 mol·l-I and 5x 10-4 mol·l-I for diazepam and chlordiazepoxide, respectively. TAYLOR andLAVERTY (1969, 1973) found the uptake or 3H-NA into synaptosomes of rat hypothalamus hardly affected by even high concentrations of benzodiazepines.…”
Section: Noradrenaline (Na)mentioning
confidence: 96%
“…10 Reserpine inhibits the transport of amines into chromaffi n granules and synaptic storage vesicles 11 , 12 by binding with high affi nity to VMAT, presumably at the amine recognition site. It has been suggested that TBZ, on the other hand, binds to a site on VMAT that is different from the substrate binding site at which reserpine interacts.…”
Section: Introductionmentioning
confidence: 99%
“…Reserpine and Tetrabenazine. Reserpine and TBZ are "classical" VMAT2 inhibitors (Pletscher, 1977) that prevent the transport of amines into synaptic vesicles. Although these agents are the most widely studied, their clinical utility is relatively limited.…”
Section: B Pharmacological Manipulation Of Vesicular Monoamine Transmentioning
confidence: 99%